Fetal Sacral Ratio: A Novel Method for Prenatal Sonographic Assessment of Sacral Abnormalities. (18th November 2021) - Perlman, Sharon; Shwartz, Itai; Hazan, Yenon; Weissbach, Avichai; Gilboa, Yinon; Kravarusic, Dragan; Samuk, Inbal
Abstract : Objectives: The sacral ratio (SR) was described as a postnatal X‐ray‐based method to detect sacral abnormalities and predict functional prognosis for fecal continence in children with anorectal malformations (ARMs). The present study aimed to describe a novel method of assessing sonographic fetal sacral ratio (f‐SR) in a normal population of fetuses. Methods: Sixty three‐dimensional (3D) ultrasound reconstruction images of the sacrum obtained from routine low‐risk scans performed between 21 and 26 weeks of gestation served for measurement. The f‐SR was calculated in a coronal view as the ratio between lines drawn at the upper and lower levels of the iliac bone and the 5th sacral vertebra. Bland–Altman plots assessed the inter‐ and intrareader variabilities of measurements. Results: The f‐SR in the normal population of fetuses was 0.913 (±0.094). During the study period, three cases with ARM were examined and had a mean f‐SR of 0.55. There was good repeatability of measurements and between readers' agreement. Conclusions: The present study introduces a novel prenatal sonographic f‐SR that can be reliably calculated on prenatal 3D ultrasound with good reliability and reproducibility. Future research will identify the clinical significance of f‐SR abnormalities in ARM and their long‐term impact on continence.